Pengujian validasi bahan ajar fisika bermuatan literasi saintifik pada materi dinamika rotasi, kesetimbangan benda tegar, elastisitas dan hukum Hooke - Silvia Agustin; Renol Afrizon; Hidayati Hidayati (Universitas Negeri Padang, 2019)
The demands of the Century must have the competence of critical thinking, communicating, linking global issues and having the ability to read and write. The government's efforts to meet the demands of the century are to improve the curriculum and the School Literacy Movement program. But the reality at senior high school does not illustrate the ideal conditions. The solution of this problem is to use physics teaching materials with scientific literacy. The purpose of this research is to overcome this problem by developing physics teaching materials with scientific literacy. and determine the validity of physics teaching materials with scientific literacy. Research conducted includes the type of Research and Development. The object of this research is physics teaching material with scientific literacy about the material of rotational dynamics, rigid equilibrium, elasticity and hooke law. The data source of this research is the result of the validation of experts including physics lecturers at the Faculty of Mathematics and Natural Sciences UNP as validators. Based on data analysis from research that has been done, obtained physics teaching materials with scientific literacy about rotational dynamics, rigid equilibrium, elasticity and hooke law which are very valid with an average validity value of 90.51. So, it can be concluded that physics teaching materials that contain scientific literacy on the material of rotational dynamics, rigid equilibrium, elasticity and hooke laws are valid.